2002
DOI: 10.1002/er.770
|View full text |Cite
|
Sign up to set email alerts
|

The effect of inlet subcooling on two-phase flow instabilities in a horizontal pipe system with augmented surfaces

Abstract: SUMMARYThis research has been conducted to investigate the e!ect of inlet subcooling on two-phase #ow instabilities in a horizontal pipe system with augmented surfaces. Five di!erent inlet temperatures are used to study the e!ect of inlet subcooling for "ve di!erent heat transfer surface con"gurations. All experiments are carried out at constant heat input, system pressure and exit restriction. The e!ect of inlet subcooling on the steady-state characteristics and two-phase #ow instabilities are studied for eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Periods and amplitudes of pressure-drop type oscillations and density-wave type oscillations change depending on the heater tube configurations. The same system and experimental results are presented in Yilmaz et al [124].…”
Section: Pressure Drop Oscillationsmentioning
confidence: 87%
“…Periods and amplitudes of pressure-drop type oscillations and density-wave type oscillations change depending on the heater tube configurations. The same system and experimental results are presented in Yilmaz et al [124].…”
Section: Pressure Drop Oscillationsmentioning
confidence: 87%
“…The two phase flow instabilities have been extensively studied during the past decade. However only a fraction has been focused on horizontal heated pipes and studying the aspects of the oscillations (Stenning and Veziroglu, 1965;Yuncu, 1990;Ding et al, 1995;Comakli et al, 2002;Yilmaz et al, 2002;Cao and Kakaç, 2009;Liang et al, 2011;Fan and Hassan, 2013;Dorao et al, 2014). In addition, only a limited number of studies have been focused on the effect of the two phase flow oscillations on the critical heat flux (CHF) and heat transfer coefficient (HTC), see Table 1.…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore it was found that the periods and amplitudes of the PDO and DWO decrease with decreasing mass flow rate, and increase with decreasing inlet temperature. Yilmaz et al (2002) investigated the effect of inlet subcooling on twophase flow instabilities in a horizontal pipe system with augmented surfaces. Cao and Kakaç (2009) investigated two phase flow instabilities in a horizontal pipe.…”
Section: Introductionmentioning
confidence: 99%